________________________________________________
Step by Step Solution for Part-1:
We know that:
- The successor of a number defines one to be added to a number
- The predecessor of a number defines one being subtracted to a number
Solution:
- ⇒ (-5 + 1) + (6 - 1)
- ⇒ (-4) + (5)
- ⇒ 1
________________________________________________
Step by Step Solution for Part-2:
We know that:
Solution:
- ⇒ a - b
- ⇒ (b - 1) - b
- ⇒ (-b + 1) + b
- ⇒ -b + 1 + b
- ⇒ 1
________________________________________________
Step by Step Solution for Part-3:
- (42 - 66) - (100 - 24)
- => (-24) - (76)
- => -100
________________________________________________